PENGARUH PEMANFAATAN MEDIA CONGKLAK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN NGAGELREJO V/400 SURABAYA - 'Aini, Siti Azzah Nur; Susanto, Rudi Umar; Hartatik, Sri; Amin, Siti Maghfirotun (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
One of the reasons why elementary school teachers don't use instructional media more often is the absence of infrastructure and equipment. The usage of learning media is one of the learning strategies that is crucial to the success of a learning process. This study sought to ascertain the impact of congklak media usage on Class III students' outcomes in mathematics learning at SDN Ngagelrejo V/400 Surabaya. Pre-experimental research design, quantitative methods, and a methodology are all used in this kind of study one grup pretest -posttest design. The sample of this research is 31 students taken by saturated sampling technique. Data analysis technique using paired sample t-test. The results of this study are that there is an influence of congklak media on students' mathematics learning outcomes. This is evidenced by the results of the t test that sig (2 tailed) is 0.000 t tabel = 2.04227 is obtained. So it can be concluded that Ho is rejected and Ha is accepted. This means that there are differences in student learning outcomes before and after using congklak media on the mathematics learning outcomes to class III students at SDN Ngagelrejo V/400 Surabaya. The conclusion in this study is that there is an influence of congklak media on the mathematics learning outcomes to Grade III students at SDN Ngagelrejo V/400 Surabaya. Therefore, it is expected that teachers can use congklak media as a tool in conveying material, so that students can be interested participating in learning and student learning outcomes can increase.